From Research to Practice: Using Assessment and Early Intervention to Improve Student Success in Introductory Statistics. Issue 2 (4th May 2018) - Lunsford, M. Leigh; Poplin, Phillip L.; Pederson, JoEllen G.
ABSTRACT: In this study we used an assessment tool evaluated in a previous study to identify students who were at-risk of not being successful in our introductory statistics course. We then required these students to attend peer tutoring, early in the semester, as an intervention. While we saw a significant increase in student success for all students in this study compared with the previous study, the at-risk students who completed the required tutoring had a significantly higher increase in success than their peers.